Traditional Values In The Tetenger Kulkul Karawitan Work - Yulianti, Dewi (Terob : Jurnal Pengkajian dan Penciptaan Seni, 2024)
Ancestral heritage in the form of traditional Balinese communication tools made of wood or bamboo operates in banjar activities, especially those in Banjar Palak Sukawati. The strength and character of the sound produced by the kulkul inspired the idea of ​​a creative karawitan piece called “Tetenger Kulkul”. The karawitan art composition entitled “Tetenger Kulkul” is a Bebarongan Kreasi musical composition that uses the five-tone Bebarongan Gamelan as the medium. The purpose of creating this karawitan work is to transform an idea born from a traditional communication tool called kulkul and to describe the traditional values ​​contained in the use of the kulkul communication tool as outlined through traditional karawitan works. This traditional karawitan work "Tetenger Kulkul" is realized through a qualitative method of observation, interviews, and literature study. Then, the molding of the idea was carried out using the creation method from Alma M. Hawkins including the exploration, improvisation and formation stages. The bebarongan musical creation "Tetenger Kulkul" consists of percussion instruments often used to accompany wewali and balihan ceremonies. The “Tetenger Kulkul” percussion incorporates religious, creative, independent, communicative, and responsible values.